Assessment of Human Exposure to Five Alternaria Mycotoxins in China by Biomonitoring Approach - Kai Fan (MDPI AG, 2021)
This biomonitoring study was conducted to investigate the concentration levels of five Alternaria mycotoxins in urine samples from 269 healthy volunteers living in the Yangtze River Delta, China. Alternariol (AOH), alternariol monomethyl ether (AME), tenuazonic acid (TeA) and tentoxin (TEN) were detected in 38.3%, 48.7%, 63.9% and 23.4% of urine samples with the concentrations ranging from 0.057 to 45.8 ng/mL, 0.020 to 0.802 ng/mL, 0.050 to 80.6 ng/mL and 0.021 to 0.939 ng/mL, respectively. Altenuene (ALT) was not detected in any urine sample. Based on the urinary concentrations, the probable daily intake (PDI) values of Alternaria mycotoxins were calculated, and 100%, 99.2–100%, 0.372% and 1.12% of participants exceeded the threshold of toxicological concern (TTC) values for AOH, AME, TeA and TEN, respectively. This study revealed high potential health risks related to the contaminations of major Alternaria mycotoxins in China and highlighted the necessity for more toxicological studies to provide better basis for further comprehensive risk assessments.